化简(3+√3)/[√2-√(2-√3)]
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 01:47:33
化简(3+√3)/[√2-√(2-√3)]化简(3+√3)/[√2-√(2-√3)]化简(3+√3)/[√2-√(2-√3)](3+√3)/[√2-√(2-√3)]=(3+√3)/{√2-√[(√3-
化简(3+√3)/[√2-√(2-√3)]
化简(3+√3)/[√2-√(2-√3)]
化简(3+√3)/[√2-√(2-√3)]
(3 + √3) / [√2 - √(2 - √3)] = (3 + √3) / {√2 - √[(√3 - 1)^2 / 2 ] } = (3 + √3) / {√2 - (√3 -1) * (√2) / 2} = (3 + √3) / {√2 - (√6 - √2) / 2} = (3 + √3) / {(3√2 - √6) / 2} = 2 * (3 + √3) / (3√2 -√6) = 2 * (3 +√3) * (3√2 + √6) / [(3√2 - √6) * (3√2 + √6)] = 2 * (9√2 + 3√6 + 3√6 + 3√2) / (18 - 6) = 2 * (12√2 + 6√6) / 12 = 2√2 + √6
化简√(2+√3)
化简√(2 √3)
化简√(2+√3),
化简√3-√2
化简 √6/(√3-√2)
化简(3+√3)/[√2-√(2-√3)]
化简(√2-√3)分之(√2+√3)
化简2√6/√2+√3-√5
化简√(1-√3/2)/2
化简:(8+2√15-√10-√6)/(√5+√3-√2)
(8√+48√)(2√-12√)-(3√-2√)化简 答案是-23,
化简:√(3√2-2√3)²
化简√27分之-3√2
化简6√8×(-3√2)
√2+√3等于?化简!
化简(4√2)/(3√7)
化简:(√6+4√3+3√2)/[(√6+√3)(√3+√2)]
化简√10+√14+√15+√21分之√2+√3